SARS-CoV-2 Infection and the Newborn - Ovalı, Fahri (Frontiers in Pediatrics, 2020)
Severe Acute Respiratory Syndrome Coronavirus Type 2 (SARS-CoV-2) affects people at all ages and it may be encountered in pregnant women and newborns also. The information about its clinical features, laboratory findings and prognosis in children and newborns is scarce. All the reported cases in pregnant women were in the 2nd or 3rd trimester and only 1% of them developed severe disease. Miscarriages are rare. Materno-fetal transmission of the disease is controversial. Definitive diagnosis can be made by a history of contact with a proven case, fever, pneumonia and gastrointestinal disorder and a Polymerase chain reaction (PCR) test of nasopharyngeal swabs. Lymphopenia as well as liver and renal dysfunctions may be seen. Suspected or proven cases of newborns with symptoms should be quarantined in the neonatal intensive care unit for at least 14 days with standart and droplet isolation precautions. Asymptomatic infants may be quaratined at home. Transport of the neonates should be performed in a dedicated transport incubator and ambulance with isolation precautions. There is no specific treatment for the disease, but hemodynamic stabilization of the infant, respiratory management and other daily care are essential. Drugs against cytokine storm syndrome such as corticosteroids or tocilizumab are under investigation. Routine antibiotics are not recommended. No deaths have been reported so far in the neonatal population. Families and healthcare staff should receive pyschological support. Since the infection is quite new and knowledge is constantly accumulating, following developments and continuous updates are crucial.